The Cuban Propaganda War: The Story of Elián González - Pérez, Juan Orlando (Javnost-The Public, 2005)
Elián González, an unknown Cuban boy, became the unfortunate star of one of the greatest media stories of our time, when he appeared floating in the sea after the sinking of the boat in which he, his mother and his stepfather abandoned their country. Between December 1999 and June 2000, international media were full with reports of the dispute for the child between the Cuban exile in the United States and the government of the island, which involved the Clinton Administration and was ultimately decided by the Supreme Court. According to the polls, the story of Elián González had relevance in terms of public attention, similar to other great media stories like the Clinton-Lewinsky affaire. This article explains why a six-year old boy from a remote Cuban city, who must have had a life like any other child, outside of the world of newspapers and television news, was transformed into a media character, and the hero of a campaign of intensive political propaganda inside Cuba. The author examines the political circumstances surrounding the events and the symbolic components of the story as presented by Cuban media, particularly issues like family, race and nationality.